Pengaruh Model Problem Based Learning (PBL) Terhadap Keterampilan Berpikir Kritis Siswa pada Pembelajaran Tematik Terpadu Di Kelas V SDN 05 Jaruai Kota Padang - Suryani, Ade Irma; Hayuni, Riska (Jurnal Riset Pendidikan Dasar Dan Karakter, 2023)
This research is motivated by the critical thinking skills of students who still have difficulty solving problems in learning, students who are less active in discussing with their friends, students who still have difficulty formulating questions and use conventional media. This research aims to see the influence of the Problem Based Learning (PBL) model on students' critical thinking skills in integrated thematic learning in class V at SDN 05 Jaruai, Padang City. The type of research is Quasi Experimental Design with a Posttest Only Control Design research design. The population of this study was all class V students at SDN 05 Jaruai, Padang City for the 2021/2022 academic year with a sample of students from classes VA and VB (64 people). Data collection in this research used a critical thinking skills test in the form of objective questions totaling 17 questions. The data obtained was analyzed using the t test. Based on data analysis, the results of hypothesis testing using the t-test were obtained and showed that t_count = 2.815 and t_table = 1.670 and a significance level of 5%. Based on the test tcount > ttable (2.815 > 1.670), the hypothesis or H1 is accepted. So it can be concluded "Students' critical thinking skills using the Problem Based Learning (PBL) model are than those without using the Problem Based Learning (PBL) model in integrated thematic learning in class V at SDN 05 Jaruai, Padang City, academic year 2021/2022."